Pengaruh Gaya Kepemimpinan dan Motivasi Terhadap Kinerja Pegawai Pada PT ASDP Indonesia Fery (Persero) Cabang Ambon - Annisa, Nurul; Tuanaya, Wahab; Normawati, Normawati (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the effect of leadership style and motivation on employee performance in a government institution involving 72 respondents. A quantitative method with multiple linear regression was applied to examine the relationship between independent variables (leadership style and motivation) and the dependent variable (employee performance). The validity and reliability tests indicated that all research instruments were valid and reliable. Classical assumption tests confirmed that the regression model had no issues with multicollinearity, autocorrelation, or heteroscedasticity. Regression analysis revealed that both leadership style and motivation have a positive and significant effect on employee performance, both partially and simultaneously. These findings suggest that improving leadership quality and employee motivation can be an effective strategy to enhance organizational productivity and performance. This research is expected to serve as a valuable reference for management in developing evidence-based human resource management policies